Digital Libraries 6th Italian Research Conference, IRCDL 2010, Padua, Italy, January 28-29, 2010. Revised Selected Papers - Agosti, Maristella; Esposito, Floriana; Thanos, Costantino; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 6th Italian Research Conference on Digital Libraries held in Padua, Italy, in January 2010.
Keynote Addresses -- Digital Cultural Content: National and European Projects and Strategies -- Archival Information Systems in Italy and the National Archival Portal -- System Interoperability and Data Integration -- Making Digital Library Content Interoperable -- Integrating a Content-Based Recommender System into Digital Libraries for Cultural Heritage -- Infrastructures, Metadata Creation and Management -- Digital Stacks: Turning a Current Prototype into an Operational Service -- A First National Italian Register for Digital Resources for Both Cultural and Scientific Communities (Communication) -- FAST and NESTOR: How to Exploit Annotation Hierarchies -- A New Domain Independent Keyphrase Extraction System -- An Event-Centric Provenance Model for Digital Libraries -- A Digital Library Effort to Support the Building of Grammatical Resources for Italian Dialects -- Representation, Indexing and Retrieval in Digital Libraries -- Interactive Visual Representations of Complex Information Structures -- Mathematical Symbol Indexing for Digital Libraries -- Using Explicit Word Co-occurrences to Improve Term-Based Text Retrieval -- Semantic Relatedness Approach for Named Entity Disambiguation -- Merging Structural and Taxonomic Similarity for Text Retrieval Using Relational Descriptions -- Handling Audio-Visual and Non-traditional Objects -- Audio Objects Access: Tools for the Preservation of the Cultural Heritage -- Toward Conversation Retrieval -- Improving Classification and Retrieval of Illuminated Manuscript with Semantic Information -- Content-Based Cover Song Identification in Music Digital Libraries -- Toward an Audio Digital Library 2.0: Smash, a Social Music Archive of SHellac Phonographic Discs.
Keywords: Computer science; Information systems; Database management; Data mining; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; Database Management; Information Systems Applications (incl.Internet).; Data Mining and Knowledge Discovery; Information Systems and Communication Service